Ovulation and gestation on the right and left hand sides in crossbred dairy cows - Ferreira, Ademir de Moraes; Sá, Wanderlei Ferreira de; Vetromila, Marcos Antonio Monks (Pesquisa Agropecuaria Brasileira, 2014)
A study 1,030 oestrus cycles in crossbred dairy cows from five herds in the milk producing region of Juiz de Fora, Minas Gerais State, Brazil, was undertaken in the four year period from 1980 to 1983. Ovulations were detected by the presence of a corpus luteum in the ovaries via rectal palpation. Of the ovulations so detected, 63.6% were located in the right-hand and 36.4% in the left-hand ovary. Pregnancy diagnosis in 2,181 cows showed a similar pattern, with 70.1% on the right-hand side and only 29.9% on the left. The results indicated a predominance of ovary activity and uterine pregnancy on the right-hand side of the reproductive tract.
Keywords: bovine; reproduction; side ovulation; side pregnancy